Styles of regulators : evidence from the sec comment letters - Do, Thuc Truc (2018)
Security regulations are enforced by the SEC staff. Conceptually, the regulations shall be enforced uniformly despite enforcers’ personal differences. I offer evidence to the contrary. Using the setting of SEC filing review process, I find that SEC staff members exhibit personal “styles” in their reviews. Their personal styles significantly affect firms’ remediation costs, the contents of the SEC letter, and firms’ financial reporting quality. I find that female staff members are associated with higher remediation costs while the SEC staff members with CPA qualifications are more likely to emphasize accounting disclosures and firms under their supervision are more likely to report truthfully (lower F-score). Overall, the paper offers consistent evidence that SEC regulation enforcers exhibit individual differences and their styles affect firms’ financial reporting quality.